#TITLE_ALTERNATIVE# - Yatiman ( NIM: 305 00 201), Petrus
Abstract: Carbon steel pipe used for transporting crude oil is susceptible to general and/or localized corrosion due to the presence of brine solution. Depending on the C032-and aggressive ion (e.g. Cr ion) concentrations in the solution, thin iron(II) carbonate layer might be formed on the inner surface of the steel pipe. This layer leads to increase the corrosion resistance of the pipe. In fact, corrosion has been found to occur in several locations at which protective carbonate layer cannot be formed under localized turbulence flow of crude oil. In practice, inhibitor is purged into the flowing oil to control the steel pipe corrosion. Since this prevention method is known as the best method for controlling pipe corrosion, obtaining the most effective inhibitor remains as one of a main part of the current research interest. BenzotriazoIe (BTAH) has been reported as an effective inhibitor especially for inhibiting the corrosion of copper and copper alloys exposed in acid solutions. Even though it can also be utilized to inhibit carbon steel corrosion in a few test solutions, the investigation reports are still limited on the effect of BTAH on the anodic and cathodic reactions. Whereas, the inhibition mechanism of BTAH to prevent carbon steel corrosion in brine solution and other solutions of pH 4 has not been clarified in detail yet. BTAH dissolves both in water and oil, does not stabilized its emulsion and does not harm to environment. To assess the effectiveness of this inhibitor to addition, the change in the X-ray diffraction intensity resulted from XRD analysis can be used to assess the degradation rate of the carbon steel corrosion. The results of the research indicate that BTAH could inhibit the API 5L X65 carbon steel corrosion in the test solutions by forming the protective layer (the inhibitor adsorptive layer) on the carbon steel surface. BTAH is both the anodic and cathodic types of inhibitor in NaCl and NaCl + Na2CO3 solutions saturated with CO2. Whereas, in the Na2CO3 solution saturated with C02, BTAH is the anodic type of inhibitor. The inhibition/adsorption mechanism of BTAH on the corrosion of API 5L X65 carbon steel occurred due to interaction between a-electrons and lone pair electrons of the nitrogen (N) atoms on the triazole ring of BTAH and d orbitals of iron (Fe) from the carbon steel on the carbon steel/solution interface which subsequently forms the protective layer/film on the carbon steel surface. Depending upon the properties of solution, the behavior of the interface of API 5L X65 carbon steel/NaCI solution containing C032-/HC03-ions and inhibitor can be represented as certain electrical equivalent circuits. These electrical equivalent circuits give the information of the protectiveness of the protective layer/film. Whereas, the protective nature of the protective layer/film formed on the carbon steel surface is influenced by the concentration of Cl- and C032-/HC03 ions, the presence of inhibitor, temperature, immersion time and pH.